Pelabelan Antiajaib Berdasarkan Jarak pada Operasi Perkalian Tensor Graf - Christyan Tamaro Nadeak (Universitas Negeri Gorontalo, 2022)
Let be a graph of order n. Let be a bijection. For any vertex , the neighbor sum is called the weight of the vertex and is denoted by where N(v) is the open neighborhood of If for any two distinct vertices and then f is called a distance antimagic labelling. If the graph G admits such a labelling, then G is said to be a distance antimagic graph. This study gives a distance antimagic labelling for tensor product of two complete graph and sufficient condition so that the tensor product of a regular graph and complete graph is a distance antimagic graph.